Implementation of US Environmental Protection Agency's storm water management model (US EPA SWMM) to assess the flood drainage system of the University of the Philippines Diliman campus - Lumbera, Maxell P.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
In this period of rapid urbanization, a number of green spaces is being converted to building sites, commercial establishments, subdivisions, and parking spaces. These developments lead to land use changes which affect the well laid natural hydrology of a given area. To be able to understand the impacts of urbanization to urban hydrology, the University of the Philippines Diliman campus was selected. This study aims to assess the existing drainage system of the University of the Philippines Diliman campus using US Environmental Protection Agency's (US EPA) Storm Water Management Model (SWMM). This study considered the variations in the land cover, the anticipated effects of variable rainfall characteristics, and the implementation of new local policies. Detailed methodology was presented to delineate the urban catchment and to completely define the properties of the resulting subcatchments. In this study, GIS tools and techniques were used to quantify the properties of the subcatchments that cannot be easily assumed as they are expected to significantly vary across the study area. Junction and conduit properties were established based on the storm drainage system plan of UP Diliman obtained from UP Office of Campus Architect. To be able to determine the impacts of rainfall properties in the assessment of the existing drainage system, storms with different return periods (i.e. 2-, 3-, 10- and 25-yr) were used. Similarly, the effects of land cover changes were also investigated by altering the percent impervious of the subcatchments based on a theoretical scenario that the impervious areas expand across each subcatchment through time. Results from the simulation show that an increase in the impervious area increases the resulting runoff from the related subcatchment and thus the total inflow to be received by the drainage system also increases. This resulted to an increase in the reported system flooding which is primarily due to the amount of storm water that cannot get into the drainage network due to flooded nodes and conduits in full capacity. The Department of Public Works and Highways (DPWH) recently specifies 910 mm as the minimum size of the conduits to be used in drainage networks. Three scenarios were compared with 600, 910 mm, and 1200 mm specifications for the conduit diameters and it was found out that the response of the system generally improves as smaller system flooding was observed for a simulation using 1200 mm. However, several areas in the campus will still experience node flooding primarily because of their topographical constraints (i.e. natural draining areas). As such, increasing the conduit diameters does not improve the performance of the drainage network in these areas. It is recommended instead to establish more outfall points along the UP Lagoon. This will require structural works along the UP Lagoon to improve its efficiency. Similarly, five isolated detention ponds of dimensions 5m x 5m x 1.5 m (length x width x depth) was proposed to temporarily store the storm water generated during heavy rainfall. It is recommended however, to use optimization tools to specify the optimum size and the most applicable location for these storage facilities.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Drainage; Storm sewers; Urban runoff